Kontroversi Mushaf Utsmani - Hidayah, Ulil (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
The Quran has sailed a long history, beginning with the receipt of the divinitymessage of Muhammad which was conveyed to Muslim generations by recording itthrough memorization and writing. Initially, in teaching al Quran Muhammadused tribal dialect if necessary. Yet, after the Prophet passed away, the variousdialect of the letters in the Quran lead to confusion and dispute in society.Therefore, when Uthman became caliph, he ordered that all manuscripts bedestroyed, and formed a team of Mushaf bookkeeping led by Zaid bin Thabit.The manuscripts verified by Uthman were sent to all parts of the Islamic State.However, Ibnu Mas’ud, one of the companions who wrote manuscripts duringprophet’s era, rejected the order. He refused reading Zaid’s mushaf becauseduring Zaid’s childhood Ibnu Mas’ud had been memorizing more than seventysurahs uttered by the Prophet.Al Quran telah mengarungi sejarah panjang, diawali dengan penerimaan pesanketuhanan oleh Muhammad yang kemudian disampaikan kepada generasiIslam dengan merekamnya melalui menghafal dan menulis. Awalnya dalammengajarkan al Quran nabi Muhammad menggunakan dialek sesuai kesukuanjika dirasa perlu. Namun setelah Rasulullah wafat terdapat banyak dialek yangmenyebabkan huruf al Quran mulai menampakkan kerancuan dan perselisihandalam masyarakat. Maka pada masa khalifah Utsman, diperintahkan agarsemua mushaf dimusnahkan dan dibentuk tim pembukuan mushaf al Quranyang dipimpin oleh Zaid bin Tsabit. Naskah yang sudah di verifikasi Utsmandikirimkan ke seluruh wilayah negara Islam. Namun, Ibnu Mas’ud salahsatu sahabat yang telah menulis mushaf sejak masa nabi menolak membakarmushafnya. Dia tidak mau membaca qiraat Zaid, karena semasa Zaid masihkecil Ibnu Mas’ud telah menghafal lebih dari tujuh puluh surah langsung darilisan Rasulullah.